Dentin thickness of the mesio-buccal root wall of the lower first molar using cone beam computerized tomography (CBCT) - Đeri Aleksandra; Radman-Kuzmanović Irena; Moravac Nikola; Tejić Milan; Josipović Renata; Arbutina Adriana; Marin Saša; Trtić Nataša; Veselinović Valentina (Serbian Medical Society - Dental Section, Belgrade, 2023)
Introduction The aim of this work was to check the average thickness of dentinal wall of the mesio-buccal root of the first lower molar using CBCT axial sections of intact teeth. Material and method In this cross-sectional study, 100 CBCT images of mandibular first molars from the Promax 3Dent radiology center in Banja Luka, Bosnia and Herzegovina were evaluated. A Planmeca Promax3D Max apparatus (Planmeca, Helsinki, Finland) was used, with a field of view (FOV) of 8 × 8 cm and a resolution of 0.1 mm. Analysis was performed using Romexis Viewer software version 3.1.1 (Planmeca, Helsinki, Finland). At an axial thickness of 0.1 mm, transverse sections with a distance of 1 mm were made below the furcation area (at a magnification ×10) at a distance of 1, 2, 3, 4, 5 mm from the furcation. The data were then analyzed by paired t-test. Results The thickness of dentinal wall of the mesio-buccal root of the lower first molar was significantly smaller at 2 mm and 3 mm than when measured at 1, 4 and 5 mm (p < 0.05). There was no significant difference between measurements at 1, 4 and 5 mm below the furcation area (p = 0.001). Conclusion Due to the small thickness of dentinal wall at 2-3 mm below the furcation in the root canal, caution is required when instrumenting mesio-buccal canal of the lower first molar and correct selection of the instrumentation technique in order to avoid transportation or stripping perforation that may lead to root fracture.